Ligand-independent assembly of recombinant human CD1 by using oxidative refolding chromatography - Altamirano, Myriam M. (The National Academy of Sciences, 2001)
CD1 is an MHC class I-like antigen-presenting molecule consisting of a heavy chain and β(2)-microglobulin light chain. The in vitro refolding of synthetic MHC class I molecules has always required the presence of ligand. We report here the use of a folding method using an immobilized chaperone fragment, a protein disulphide isomerase, and a peptidyl-prolyl cis-trans isomerase (oxidative refolding chromatography) for the fast and efficient assembly of ligand-free and ligand-associated CD1a and CD1b, starting with material synthesized in Escherichia coli. The results suggest that “empty” MHC class I-like molecules can assemble and remain stable at physiological temperatures in the absence of ligand. The use of oxidative refolding chromatography thus is extended to encompass complex multisubunit proteins and specifically to members of the extensive, functionally diverse and important immunoglobulin supergene family of proteins, including those for which a ligand has yet to be identified.